Breast cancer under control – risk calculators - Beata Pepłońska; Filip Turoboś (Medycyna Pracy)
Breast cancer is the most common malignancy in women. Over several decades of research, it has been determined which individual characteristics or exposure increase the likelihood of developing breast cancer. The co-occurrence of several factors is associated with a higher risk of developing this cancer. The ability to identify women whose accumulation of unfavorable factors causes a high risk of developing breast cancer is important for prevention, screening tests and also for medical doctors providing preventive care. For this purpose, many risk prediction models (risk calculators) have been developed. The aim of the manuscript was to discuss the most frequently used breast cancer risk calculators, paying particular attention to information about the risk factors they take into account, the method of interpreting the obtained results, the populations in which they are used and data from validation studies. Med Pr Work Health Saf. 2024;75(6):531–544